The fragmentation of the right to freedom of expression and the Brazilian Democratic State in the Bolsonaro government (2018-2022) - Rosso Nelson, Rocco Antonio Rangel (2024)
The present study deals with the theme of democracy, addressing its association with the right to freedom of expression as an indicator of the level of democracy in the State.